Changing profile of public administration - Dogra, Arti (2006)
Over the last few years, a lot oc changes have been witnessed in the field of public administration. A number of philosophers, academicians and public functionaries have been involved in the study of public administration and in suggesting new ways and means to bring about an improvement in the functioning of administration. An attempt has been made to discuss the various steps which were taken to change the profile of public administration to ensure efficiency and effectiveness in the functioning of the bureaucracy. Various conferences such as Minnowbrook-II Conference, CAPAM Conference, International Conference of Administrative Sciences have been instrumental in bringing about a change in the field of public administration. David Osborne and Ted Gaebler have made remarkable contribution. Their concept of `public entrepreneurship have been discussed. One of the major steps to change the profile of public administration has been the introduction of the New Public Management paradigm. Keeping in view the developments which took place over the years, an attempt has been made to find out what the Government of India did to ensure efficiency in administration. - Reproduced.
Keywords: Public administration